Análise de tendências hidrológicas na bacia do Rio das Mortes e suas relações com as mudanças na cobertura do solo - Rosin, Cássia (2015)
The Mato Grosso Cerrado suffered intensive deforestation process from the 60s, by Federal Government initiatives combined with international interests aimed at the development of agriculture in this region. Current estimates indicate that there is a remnant of only 55% of Cerrado, however, the agricultural frontier continues to expand, committing these areas that are still preserved. Much of the results found in the literature on the effects of vegetation removal are for tropical forests and watersheds yet for less than 1 km². To the Amazon rainforest, were conducted several studies on deforestation. However, there are few studies on the effects of the transformation of the Cerrado in agropastoral landscape. Therefore, this study intends to correlate the change of land cover with the temporal variation of precipitation and flow in the Rio das Mortes. To evaluate possible hydrological changes were used series of precipitation and flow averages, monthly and annual daily maximum and minimum of dry and wet periods, for which there was the Mann-Kendall trend analysis. Having the monthly series of daily rainfall and runoff data were prepared averages consecutive decadal, which were presented in bloxplot graphics and the average of the three periods (1975-1984, 1985-1994, and 1995-2004) were compared by Student's t-test. For assessment of land cover were used images of 12-point orbits of Landsat 5 TM sensor, with decadal interval, from 1984, 1994 and 2004. The images were pre-processed and classified by the nearest neighbor algorithm. Analysis Mann-Kendall trends for rainfall was insignificant time series resulting in only 11% of the series with significant trends suggesting that the local climatological system depends very little evaporation of surface area. Analyses of Mann-Kendall trend for fluviometric time series presented both negative and positive trends. The station whose analyzes presented in all negative trend series shows strong connection with the type of use and over-exploitation of water resources. Already in the stations showed an increasing trend, we note that the type of use and the physical characteristics of the soil influence the water dynamics in the basin. Analyzing the areas of native vegetation of the Rio das Mortes Basin, it appears that there was a reduction of the same in 1984, 1994 and 2004, which correspond, respectively, to 79%, 71% and 57% of the area. While the classes expressing anthropic use in 1984 occupied 21% of the basin and in 2004 came to occupy 43% of the basin area of Rio das Mortes. The reduction of native vegetation and increased anthropogenic use classes occurred more intensely in the Upper Rio das Mortes region, resulting in change of flow that decreased flow due to the over-exploitation. However, analysis of rainfall stations shows great variability in the precipitation, which suggests that local climatological system can be increased reliance on air flow patterns that the evaporation surface area.